Analisis Pengembangan Desa Parit Raja Kecamatan Sejangkung Perspektif Ekonomi Pembangunan Islam - Sari, Debby Puspita; Sukmawati, U. Sulia; Gustina (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2024)
This research is motivated by Village Development and Development in Parit Raja Village, Sejangkung District, seen from the level of Village independence as measured based on the Village Development Index (IDM). This research aims to analyze the concept of village development from an Islamic economic development perspective. The theory used in this research is Ibn Khaldun's Development Economic Theory. This research uses a qualitative research approach which is field research in nature and tends to use analysis which emphasizes process and meaning. The data collection techniques used were observation, interviews and documentation. The data source used is primary. Research data analysis techniques are data reduction, data presentation, drawing conclusions. Based on the results of this research, it is concluded that Parit Raja Village has implemented the concept of Islamic development economics which consists of 5 variables including state, institutions, human beings, wealth, and justice and development.